Analisis pelaksanaan pada manajemen pembelajaran proyek penguatan profil pelajar Pancasila dalam menumbuhkan kemampuan bernalar kritis dan kreatif peserta didik fase C - Dea Pangesti; Sri Marmoah (Didaktika Dwija Indria, 2025)
The management implementation stage is the implementation of planning and realizing characteristics of the profile of Pancasila students. Implementation of P5 activities at SDN 04 Jatingarang has not been consistent. Observations showed during P5 activities, students were less enthusiastic about learning, had low curiosity, and were not yet able to explain the reasons for their ideas. This study aimed to determine the implementation of P5 learning management in fostering critical and creative reasoning skills in phase C students. The method was descriptive qualitative, with data collection techniques in observation, interviews, documentation, and questionnaires. The data sources were the principal, grade V teachers, and grade V students of SDN 04 Jatingarang. The outcomes of the study showed the implementation at SDN 04 Jatingarang consisted of the stages of initiating, implementing, and closing activities. Fostering creative and critical reasoning skills is done by getting used to discussing and providing challenges with gradual levels of difficulty. The average creative ability at the implementation stage is in the fairly creative category. Critical reasoning ability, at the P5 implementation, the average student is in the sufficient category. Good learning management can develop students’ abilities and skills that align with the character profile of Pancasila students.